2009
DOI: 10.1016/j.jpainsymman.2009.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Self-Management of Pain, Dyspnea, and Cough in Cystic Fibrosis

Abstract: Cystic fibrosis (CF) has been transformed from a fatal diagnosis in infancy to a chronic disease of children and young adults. Symptom patterns and disease burden in CF may be shifting to reflect the relatively healthier, older population with the disease. Self-management of symptoms is a hallmark of chronic illness, and yet we do not have a good understanding of how CF patients monitor or manage their symptoms. Children and adults were recruited through clinics in three Canadian provinces. Questionnaires with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 16 publications
2
67
0
1
Order By: Relevance
“…Sleep disturbance is not a direct symptom of CF, but coughing has been found to interfere with sleep . It is important to note, however, that a causal relationship between cough and sleep disturbance has not been substantiated .…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Sleep disturbance is not a direct symptom of CF, but coughing has been found to interfere with sleep . It is important to note, however, that a causal relationship between cough and sleep disturbance has not been substantiated .…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Interestingly, previous studies assessing the general symptom of pain in CF indicate that its most common location was the abdomen [811]. Nevertheless, most of these studies did not differentiate abdominal pain e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pain in CF may be due to musculoskeletal changes (Aris et al, ; Tattersall and Walshaw, ) as well as CF‐related arthropathy (Botton et al, ; Hubbard et al, ; Koch et al, ). Previous studies found back pain and headaches reported in up to 89% of adults with stable CF, while the incidence of chest pain varies between 16% and 64% (Rose et al, ; Epker et al, ; Festini et al, ; Flume et al, ; Sermet‐Gaudelus et al, ; Stenekes et al, ). However, the influence of lung disease severity on pain locations is unknown.…”
Section: Introductionmentioning
confidence: 99%